The risk of osteoporotic fractures after gastrectomy: Findings from the Korean national sample cohort database (2002-2019) - Yun, Il; Hurh, Kyungduk; Jeong, Sung Hoon; Park, Eun-Cheol; Jang, Sung-In (Frontiers in Oncology, 2022)
Objective: This study used a national sample cohort database to investigate the risk of osteoporotic fractures after gastrectomy is performed for gastric cancer. Materials and Methods: We used data from the Korea National Health Insurance Service-National Sample Cohort between 2002 and 2019. After performing 1:3 propensity score matching, 28,328 individuals were analysed in the final study (7, 082 cases; 21, 246 controls). Gastrectomy data were extracted from the coded claims data, and osteoporotic fractures were defined as the occurrence of fractures in any of the vertebrae, distal radius, humerus, or hip, according to the 10th version of the International Classification of Diseases. A Cox proportional hazards regression model was generated to investigate the association between gastrectomy and risk of osteoporotic fractures. Results: Patients with gastric cancer who underwent a gastrectomy had a higher risk of osteoporotic fractures as compared to the general population (men, hazard ratio [HR]: 1.13, 95% confidence interval [CI]: 1.00-1.27; women, HR: 1.18, 95% CI: 1.06-1.30). A significantly higher risk of osteoporotic fractures was observed with surgical resection than with endoscopic resection (men, surgical, HR: 1.28, 95% CI: 1.08-1.52, endoscopic, HR: 1.04, 95% CI: 0.90-1.21; women, surgical, HR: 1.34, 95% CI: 1.11-1.62, endoscopic, HR: 1.13, 95% CI: 1.01-1.27). In men, the risk of hip fracture was the highest among the four fracture sites (HR: 1.18, 95% CI:0.89-1.56), while in women, the risk of vertebral fracture after gastrectomy was the highest (HR: 1.16, 95% CI: 0.99-1.35). Conclusion: Patients with gastric cancer who underwent gastrectomy had a higher risk of osteoporotic fractures as compared to the general population. This suggests the need for bone metabolism management in patients with gastric cancer to prevent post-gastrectomy complications.